2017
DOI: 10.1016/j.jlumin.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the nanoscale structure and the optical properties of Ce-doped SiO 1.5 thin films

Abstract: Cerium doped SiO x (0 ox o 2) thin films have emerged as promising materials for future Si-based blue light emitting devices. The optical properties of these films are strongly dependent on the nanoscale structure such as the spatial distribution of the Ce atoms. These issues have remained difficult to observe in practice by conventional techniques. In this work, we propose to use atom probe tomography which has emerged as a unique technique that is able to provide information about the chemical composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…The diameter of isolated Si-ncs for sample Si 4% , Si 9% and Si 16% can be considered as constant (Fig. 3 b) and are compatible with the constant PL peak position under the hypothesis that only isolated Si-ncs are responsible of the PL emission as previously demonstrated on Cedoped SiO 1.5 system [24]. In this case, the authors evidenced a luminescence quenching of Si-ncs in the vicinity of rare-earth silicate particles and attributed the optical emission to only isolated Si-ncs.…”
Section: Photoluminescence Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…The diameter of isolated Si-ncs for sample Si 4% , Si 9% and Si 16% can be considered as constant (Fig. 3 b) and are compatible with the constant PL peak position under the hypothesis that only isolated Si-ncs are responsible of the PL emission as previously demonstrated on Cedoped SiO 1.5 system [24]. In this case, the authors evidenced a luminescence quenching of Si-ncs in the vicinity of rare-earth silicate particles and attributed the optical emission to only isolated Si-ncs.…”
Section: Photoluminescence Analysissupporting
confidence: 85%
“…By counting the number of atoms of each species in the sampling box, we are able to identify the composition of the Er-rich nanoparticles. The resulting compositional measurements are listed in [14,24]. This important result demonstrates similar phase transformation characteristics for two different rare earths in silicon-enriched silica.…”
Section: Clusters Analysismentioning
confidence: 56%
“…Implanted stoichiometric Si 3 N 4 films that contained no nc‐Si exhibited a red shift in PL emission after heat treatment but the PL intensity remained weak. This further supports that the observed enhancement is due to an interaction between Ce and nc‐Si and is not a result of emission from the SiN x , Ce ions, or Ce‐silicates …”
Section: Resultssupporting
confidence: 77%
“…APT analyses and TEM experiments have shown the phase separation, which began at 800 °C (figure 5), between Si-rich and Hfrich phases; these results are attributed to SiO 2 -rich and HfO 2 -rich phases, respectively. Contrary to the RE 3+ doping of SiO x matrices for which a precipitation of RE ions in the form of clusters was evidenced in the case of Er 3+ and Ce 3+ doping by the formation of RE silicates [20,39], the presence of Pr 3+ ions in the matrix does not lead to the formation of Pr oxides or Pr silicates during the annealing process at high temperature. We observed that Pr 3+ ions tend to diffuse into the HfO 2 -rich phase from the beginning of the phase decomposition, and are already present in the HfO 2 -rich phase at 800 °C.…”
Section: Discussionmentioning
confidence: 69%